Bank Indonesia's Behavior in Response to The Fed’s Policy - Kiky Indah Sari; Telisa Aulia Falianty (Jurnal Ekonomi dan Studi Pembangunan, 2025)
Global economic instability is a challenge for the domestic economy, especially for emerging countries. A higher Federal Funds Rate for longer affects economic stability. Bank Indonesia plays a role in determining the BI rate to achieve economic goals. Indonesia as an open economy needs to consider external aspects in determining monetary policy. The Augmented Taylor Rule framework can facilitate this need to know about the determination of the BI rate. This study aims to identify the behavior of Bank Indonesia in response to the Fed's policy and the phenomenon of higher for longer. The research period was conducted from 2000Q2 - 2023Q4 using secondary data. The results of the analysis show that overall Bank Indonesia responds to an increase in the BI rate when the inflation gap increases, the output gap increases, and the rupiah depreciates. These conditions are following the Taylor Rule framework. However, in the higher for longer period there is a change in which the determination of the BI rate depends only on the output gap and the real exchange rate. The inflation gap variable has no significant effect on the determination of the BI rate. In the higher for longer period, the prioritized economic goal is a comprehensive economic recovery.